The effect of using smartphone media and learning activities on collaborative abilities and learning outcomes - Sutarum Martowijono; Akhmad Qomaru Zaman (Journal of diversity in learning (JDIL), 2022)
This study aims to determine the differences in the use of smartphone media for students with disabilities on collaboration abilities and learning outcomes. Experimental research using comparative testing in two different classes with a sample of special school students in the Lamongan district. The results show that collaborative activities increase collaboration and foster motivation in learning by using smartphones, but the use of smartphones has little effect on their learning outcomes. This is because students with disabilities have not been able to understand learning procedures using smartphone media.